Perspectivas de profissionais dos serviços de acolhimento institucional sobre o direito à convivência familiar e comunitária - Soares, Thamires Pinto (Brasil, 2016)
This paper aims to discuss the right of family and community life from a historical analyses of social care policies for children and teenagers who live in poverty, and the context of institutional care related to this group. Therefore, three different social care services from the same municipality have been investigated through semi-structured interviews with the professionals and participant observation. The sample collected was organized into the following categories: (1) General characteristics of the institutions, (2) Public attended, (3) Work with families, (4) Community Living and (5) Articulation with other institutions. The analysis was based on dialectical historical materialism. The units operate in the institutional shelter model, and children and adolescents received are distributed according to their age and groups of siblings. The families attended are characterized by experiencing poverty, low education, drug use, family violence, among other difficulties. Thus, the social work seeks to overcome these problems and to strengthening family ties, so the child can return to family living. The contact between kids and families is maintained, as well as the community living. Finally, the articulation with other institutions shown to be essential for the resolution of cases. The results show that, despite some difficulties perceived on the services studied, it is possible to conclude that they intend to soften the paradigm established by the Child and Adolescent Statute and the National Plan for Family and Community Living, in order to overcome the exclusionary practices of social coexistence. Improvements which can guarantee the right of family and community life are still needed.
Keywords: Acolhimento institucional; Crianças e adolescentes; Convivência familiar e comunitária; Políticas sociais; CNPQ::CIENCIAS HUMANAS::PSICOLOGIA